2019
DOI: 10.1186/s12913-019-4642-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of prescription drug monitoring programs at reducing opioid-related harms and consequences: a systematic review

Abstract: BackgroundIn order to address the opioid crisis in North America, many regions have adopted preventative strategies, such as prescription drug monitoring programs (PDMPs). PDMPs aim to increase patient safety by certifying that opioids are prescribed in appropriate quantities. We aimed to synthesize the literature on changes in opioid-related harms and consequences, an important measure of PDMP effectiveness.MethodsWe completed a systematic review. We conducted a narrative synthesis of opioid-related harms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 46 publications
3
60
0
Order By: Relevance
“…74 A more recent systematic review, however, found no consistent association between population-level opioid-related harms (including heroin use and overdoses) and PDMP CDSSs. 85 We also noted a conflict of interest in some studies where the developers were also the evaluators. Systematic reviews in other fields have demonstrated that when the CDSS evaluator is also the developer, outcomes are better.…”
Section: Discussionmentioning
confidence: 99%
“…74 A more recent systematic review, however, found no consistent association between population-level opioid-related harms (including heroin use and overdoses) and PDMP CDSSs. 85 We also noted a conflict of interest in some studies where the developers were also the evaluators. Systematic reviews in other fields have demonstrated that when the CDSS evaluator is also the developer, outcomes are better.…”
Section: Discussionmentioning
confidence: 99%
“… 34 While state variability cannot be controlled by the institution, the ease of use at each institution is often a topic of consideration when exploring how to improve the effect of the PDMP. 31 Oftentimes, information in the PDMP is unorganized or challenging to analyze during a busy ED workflow. 35 In addition, clinician training on how to use the PDMP also varies at each institution, often leaving busy emergency physicians with limited expertise regarding efficient use and extraction of pertinent data from the typically external PDMP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we acknowledge the potential for adverse consequences resulting from rapid reduction or withdrawal of prescriptions for people taking opioids that have been observed elsewhere, including the USA and Canada, such as a shift towards use of illicit opioids [15,16,17]. We also recognise that each country is unique and may have specific drivers for opioid prescribing which require tailored and patient-focussed responses.…”
Section: Implications For Policy and Practicementioning
confidence: 96%
“…It also reflects the cultural and social standpoints and practices of clinical, legal and regulatory communities which fluctuate over time, as documented in the narrative review by Rosenblum and colleagues [14]. Some countries, including the USA and Canada, have responded to these concerns through increased monitoring or regulation of these prescriptions, although these measures have been associated with some unwelcome, unintended consequences such as increased use of illicit opioids [15,16,17].…”
Section: Introductionmentioning
confidence: 98%